Socialization institutions and their role in immunizing the school environment from the scourge of drugs - ZAHZAH, Khaled (Social Sciences Journal)
Drug addiction in the school environment constitutes one of the most significant challenges threatening the educational and formative process, due to its negative effects on students’ behavior and academic trajectory. This article aims to shed light on the role of various socialization institutions in preventing this scourge, through a theoretical approach based on the descriptive-analytical method. The study concludes that the functional integration of the family, school, media, religious and cultural institutions, as well as health and security agencies, represents a fundamental factor in raising awareness about the dangers of drugs and in creating a safe and supportive school environment that helps curb the spread of this phenomenon